Suppression of autophagy impedes glioblastoma development and induces senescence. Issue 9 (1st September 2016) - Gammoh, Noor; Fraser, Jane; Puente, Cindy; Syred, Heather M.; Kang, Helen; Ozawa, Tatsuya; Lam, Du; Acosta, Juan Carlos; Finch, Andrew J.; Holland, Eric; Jiang, Xuejun
ABSTRACT: The function of macroautophagy/autophagy during tumor initiation or in established tumors can be highly distinct and context-dependent. To investigate the role of autophagy in gliomagenesis, we utilized a KRAS-driven glioblastoma mouse model in which autophagy is specifically disrupted via RNAi against Atg7, Atg13 or Ulk1 . Inhibition of autophagy strongly reduced glioblastoma development, demonstrating its critical role in promoting tumor formation. Further supporting this finding is the observation that tumors originating from Atg7 -shRNA injections escaped the knockdown effect and thereby still underwent functional autophagy. In vitro, autophagy inhibition suppressed the capacity of KRAS -expressing glial cells to form oncogenic colonies or to survive low serum conditions. Molecular analyses revealed that autophagy-inhibited glial cells were unable to maintain active growth signaling under growth-restrictive conditions and were prone to undergo senescence. Overall, these results demonstrate that autophagy is crucial for glioma initiation and growth, and is a promising therapeutic target for glioblastoma treatment.